Kesenjangan Antara Ketidakpahaman dan Keberanian Bertanya: Studi Tentang Perilaku Diam Siswa dalam Pembelajaran di Sekolah Dasar - Desy Ari Sandi; Anindya Puspa Dewani; Rika Mellyaning Khoiriya; Vendy Hermanto (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2026)
This study aims to describe the gap between students' incomprehension and the courage to ask questions in the learning process in elementary school. The study used a descriptive qualitative approach with the subjects of four grade IV students of SDN 4 Panggungrejo who were selected based on the tendency of silent behavior during learning. Data were collected through semi-structured interviews regarding students' experiences when they did not understand the material, the reasons for not asking questions, and the conditions that could encourage their courage to ask. Data is analyzed through the stages of data reduction, data presentation, and conclusion drawn. The results of the study show that students often have difficulty understanding the material, especially in the subjects of Javanese, Indonesian, and Mathematics. Students are more comfortable asking questions to their classmates than to the teacher because the atmosphere is more relaxed and less stressful. This study concludes that students' silent behavior is not only influenced by their lack of understanding of the material, but also by psychological, social, and environmental factors. Therefore, teachers need to create a safe, comfortable, and supportive classroom atmosphere for students to be more daring to ask questions.